Do bulls experience pain or stress during electroejaculation? Evidence from electroencephalography, behavioral, hormonal, and metabolite profiling - Kaka, Ubedullah; Degu, Nurhusien Yimer; Kumar, Pavan; Abubakar, Abubakar Ahmed; Goh, Yong-Meng; Aslam, Muhammad Waseem; Bhutto, Khaleeq Ur Rehman; Basit, Muhammad Abdul; Qadi, Wasim S. M.; Misnan, Norazlan Mohmad; Mediani, Ahmed; Hua, Khor Kuan (Veterinary World, 2025)
Background and Aim: Electroejaculation (EE) is widely used for semen collection in bulls but raises concerns about animal welfare due to potential pain and stress. The physiological impact of EE on bulls remains a topic of debate, with previous studies yielding inconclusive results. This study aims to objectively evaluate pain and stress responses in bulls subjected to EE using electroencephalography (EEG) alongside hormonal, behavioral, and metabolite profiling. Materials and Methods: Eight bulls were subjected to EE in three replicates, with physiological and behavioral data collected before, during, and after the procedure. EEG parameters, including median frequency (MF) and total power (Ptot), were analyzed to assess cortical activity indicative of pain and stress. Blood samples were evaluated for stress-related hormones (adrenaline, noradrenaline, β-endorphin, and dopamine), while metabolomic analysis was conducted to identify biochemical alterations associated with stress. Behavioral indicators, including vocalization and muscle spasms, were recorded. Results: EE induced significant increases (p < 0.05) in stress hormones at ejaculation, which gradually returned to baseline 20 min post-procedure. EEG metrics, such as MF and Ptot, significantly increased during EE (p < 0.05), indicating heightened cortical activity associated with nociception. Metabolomic analysis revealed distinct biochemical shifts, with variations in glucose, taurine, and norepinephrine profiles across baseline, stimulation, and recovery phases. Behavioral observations corroborated physiological findings, with bulls exhibiting signs of discomfort, such as struggling, arched back posture, and excessive salivation. Conclusion: The combined EEG, hormonal, and metabolomic findings confirm that EE is a stressful and painful procedure for bulls. The study provides robust evidence of neurophysiological and biochemical responses indicative of pain. These findings highlight the need for alternative semen collection methods to minimize animal distress and improve welfare standards.